Safety and efficacy of brachial approach for coronary angiography and percutaneous coronary intervention - Islam Ghanem; Mohamed Mesbah; Hesham Refaat (The Egyptian Heart Journal, 2024)
Abstract Background There are many percutaneous coronary approaches. The most commonly used one is the radial artery because of its lowest risk of adverse vascular events. However, it could not be an option in some situations as congenital radial artery hypoplasia and spasm. In these cases, the second most common access is the femoral artery. The current literature over the brachial artery access is controversial. Thus, the aim of this study was to verify the brachial artery approach's effectiveness and safety. Results We studied 300 patients who underwent elective coronary angiography and angioplasty in our institution with failed radial access between August 2022 and February 2023. They were classified into two groups; 150 patients with brachial access and 150 with femoral access. Access, procedural and fluoroscopy times were recorded. All patients were examined carefully immediately after the procedure and before discharge to assess any complications. Left brachial access was used more frequently than left femoral access (32.7% vs. 22.7%, P = 0.05), but no significant difference noted regarding right sided or bilateral access. Procedure time, fluoroscopy time, and contrast volume did not significantly differ (P = 0.19, 0.06 and 0.1 respectively). However, brachial group had shorter access time (2.6 ± 1.1 vs. 3.4 ± 0.7 min, P = 0.05) and hospital stay (3.5 ± 1.1 vs. 5.9 ± 1.3 days, P  < 0.001). Regarding major and minor complications (especially hematomas), they were significantly less in the brachial arm (P = 0.04 and P = 0.05, respectively). Conclusions Brachial access is a safe, efficient and non-inferior to the femoral route for coronary intervention whenever radial access is not an option.